EFFICIENCY COMPARISON BETWEEN DIFFERENT ALGORITHMS FOR MAXIMUM POWER POINT TRACKER OF A SOLAR SYSTEM - Selim Mahmud and 5Md. Tanvir Yeasin, Md. Hasibur Rahman, Swadesh Poddar, 3Mohammad Mahbubur Rahma (International Journal of Scientific Research and Management (IJSRM), 2013)
There are several maximum power point tracking algorithms available such as Perturb and Observe, Incremental and Conductance, Current Sweep and Constant Voltage method etc. Here we’ll discuss few new techniques based on FL, Stimulated Annealing and Particle Swarm Optimization. And will show a comparative study with Genetic Algorithm. These techniques are as simple as the conventional one, mentioned above and yet these can successfully encounter the oscillation problem and steady state error even under adverse environment with more than 98.5% efficiency. These ideas will simplify the hardware complexity through the help of programmable microcontrollers